Report of the Working Group on Finance for Housing Sector for Eighth Plan (1992—97) - Planning Commission (Planning Commission, 1992)
Despite the quantitative growth and qualitative improvement in housing stock in the country, the magnitude of housing problem in the form of backlog as well as poor condition of existing stocks continues to be daunting. Housing activity requires to be given high priority, because it satisfies a basic human need and also contributes significantly to the employment generation and productivity improvement both directly and indirectly through linkage. effects on the other sectors of the economy.
Planning Commission